Permafrost and related engineering problems - Brown, R. J. E.; Johnston, G. H. (1964)
Roughly one-fifth of the world's land area is subject to permafrost, that is, perennially frozen ground. It is particularly important in the Soviet Union and in Canada, each of which has roughly half of its territory affected. Permafrost not only poses questions of great geophysical interest but presents the civil engineer with many exceedingly difficult problems. This article reviews the principles governing the distribution of permafrost and some of the ways of overcoming the difficulties. Environ un cinquième des terres émergés du globe sont formé es de pergélisol, c'est-à-dire de terres éternellement gelé es. A cet égard, l'Union soviétique et le Canada viennent en tête, avec chacun près de la moitié de son territoire ainsi constitué. Le pergélisol soulève des problèmes gé ophysiques très intéressants; mais, d'autre part, il pré sente à l'ingénieur civil d'énormes difficultés. Cet article étudie les principes qui régissent la répartition du pergélisol et expose quelques-unes des solutions adoptées pour résoudre les diffcultés. Peer reviewed: No NRC publication: Yes